Research on algorithms of physics-based cloth simulation - Qian, Ziyun; Jiang, Yang; Yuan, Ruisheng; Tang, Minzhe; Wang, Shunli; Wang, Shuaibing; Kou, Dongliang; Li, Mingcheng; Shan, Weihua; Yan, Zhe; Li, Run; Zhang, Lihua (SPIE, 2023)
Physics-based cloth simulation is a classic topic in computer graphics, which aims to simulate realistic cloth effects in virtual environments. In recent years, the rapid development of virtual reality has put forward higher requirements for physics-based cloth simulation, and this technology has played an increasingly important role. This paper first introduces the fundamental knowledge of cloth simulation, then summarizes the existing mainstream methods in this field. We give a classification of these works and provide an overview of each one of them. We have also conducted a large number of experiments to compare the performance of several typical algorithms. Towards the end of the article, we identify some existing limitations in this field and provide targeted suggestions for future development.